Evaluation of sediment properties using wind and turbidity observations in the shallow tidal areas of the Venice Lagoon. Issue 7 (22nd July 2014) - Venier, Chiara; D'Alpaos, Andrea; Marani, Marco
Abstract Sediment deposition and erosion by wind waves and tidal currents, mediated by bed sediment properties and by biostabilization/bioturbation, are key processes governing the dynamics of intertidal geomorphology. Here we develop and apply a method to estimate bed sediment properties, such as the settling velocity and the critical stress for erosion, providing a measure of the response of the system to the actual wave/tidal forcing. The method obtains estimates of sediment properties indirectly, by solving a sediment mass conservation equation for the water column, after explicitly modeling wave‐ and current‐induced bottom shear stresses. We apply this approach using meteorological, tidal, and turbidimetric data from a network of sensors in the Venice Lagoon, yielding estimates which compare favorably with existing observations of sediment properties. Advantages of the method are that it does not interfere with the biological and physical status of the sediment surface and that it makes use of commonly available weather and wave observations. The proposed method lends itself to the continuous monitoring of sediment parameters at the system scale with limited operational effort when the sediment suspended in the water column is mostly originated by local resuspension, such as in the case of wave‐dominated estuaries.